Rapid drug detection equipment based on molecular imprinting and surface plasmon resonance technology - Yu, Hong Jiang; Luo, Wei Li; Liu, Xuan; Li, Nan; Kong, Qing Bo (Frontiers in Chemistry, 2025)
This study develops high-sensitivity drug detection equipment combining molecular imprinting technology (MIT) and surface plasmon resonance (SPR) for rapid methamphetamine hydrochloride (MAPA) analysis. The MIT-SPR sensor chip exhibits a detection limit of 2.97×10−12 g/mL (0.003 ng/mL), maintains 98.5% sensitivity after 50 days, and achieves 97.3–101.7% recovery in dust samples. The chip demonstrates excellent reusability (8 adsorption-elution cycles) and specificity, with minimal cross-reactivity to structural analogs. Three field-deployable devices were designed for wastewater monitoring, multi-channel sampling, and portable dust detection, enabling real-time data transmission to law enforcement. Compared to traditional methods (e.g., GC, HPLC), this system offers superior sensitivity, faster response (6–10 min), and minimal sample pretreatment. The technology supports diverse sample types (sewage, organic liquids, dust) and reduces false alarms, enhancing anti-drug operations.